The handbook of communication and corporate social responsibility - Ihlen, Oyvind; Bartlett, Jennifer L.; May, Steve (Steve Kent) 1961- (Handbooks in communication and media, 2014)
"This book represents the definitive research collection for corporate social responsibility communication, offering cross-disciplinary and international perspectives from the top scholars in the field. Addresses a gap in the existing CSR literature Demonstrates the relevance of effective CSR communication for the management of organizations The 28 contributions come from top scholars in public relations, organizational communication, reputation management, marketing and management"--Provided by publisher.